The Role of Religious Education in Forming Social Consciousness - Ma'fiyah*, Ma'fiyah; Yunus, Yunus; Fadli, Subhan (Universitas Syiah Kuala, 2024)
This research describes Islamic Religious Education as related to the lack of religious education for minority students. This research is qualitative research that uses a pedagogical approach. The data source in this research comes from interviews, while the parties interviewed were the principal, teachers, students and parents. Meanwhile, secondary data is taken from documents related to research. The research results show that a. Awareness of success can be seen from the practice or implementation of the school principal's plan regarding religious education, there is no prohibition on Muslim students from praying, in fact the school always holds Islamic religious activities. Social Success is seen from the elements found in the field, namely the relationship between teachers, teachers and students who appear close in intimacy without distinguishing between each other. The school's strategy in providing understanding of religion to Muslim students apart from teaching at school is through friendship by building communication with interfaith students leaders, religious institutions, educational institutions as well as through a socio-cultural approach and management of educational units to accept all Muslim to school without special requirements, and provide services to students regardless of ethnicity and religion.